Respostas
respondido por:
11
Equação Biquadrada
+ 5x² + 4 = 0
(x²)² + 5x² + 4 = 0
substituir x² por y
y² + 5y + 4 = 0
Resolver por Bháskara
a = 1
b = 5
c = 4
Δ = b² - 4.a.c
Δ = 5² - 4 .1 . 4
Δ = 25 - 16
Δ = 9
y = - b + - √Δ/2a
y = - 5 + - √9/2.1
y = - 5 + - 3/2
y' = - 2/2 ⇒ y' = - 1
y" = - 8/2 ⇒ y" = - 4
substitui x² por y
x² = - 1 ⇒ x = + - √ - 1 ∉ R
x² = - 4 ⇒ x = + - √ - 4 ∉ R
S = { Ф}
+ 5x² + 4 = 0
(x²)² + 5x² + 4 = 0
substituir x² por y
y² + 5y + 4 = 0
Resolver por Bháskara
a = 1
b = 5
c = 4
Δ = b² - 4.a.c
Δ = 5² - 4 .1 . 4
Δ = 25 - 16
Δ = 9
y = - b + - √Δ/2a
y = - 5 + - √9/2.1
y = - 5 + - 3/2
y' = - 2/2 ⇒ y' = - 1
y" = - 8/2 ⇒ y" = - 4
substitui x² por y
x² = - 1 ⇒ x = + - √ - 1 ∉ R
x² = - 4 ⇒ x = + - √ - 4 ∉ R
S = { Ф}
daisycastro:
De nada, bons estudos! :-))
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás